2007
DOI: 10.1007/s10535-007-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

Soapwort oxidoreductase is involved in trinitrotoluene detoxification

Abstract: Plant enzymes participating in degradation of nitroaromatic compounds have not been biochemically characterized in details so far. From suspension culture of soapwort (Saponaria officinalis L.) we isolated a novel plant oxidoreductase involved in degradation of trinitrotoluene (TNT). The enzyme catalyses first steps of reduction of TNT nitro groups in the presence of NAD(P)H under anaerobic conditions. The enzyme is monomeric with molecular mass 29 kDa, its two isoforms have pI 4.8 and 5.1. According to the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…For more accurate and precise studies on phytoremediation, aseptic cultures of plants provide a convenient and efficient alternative [10]. The cell suspension cultures proved to be an effective tool for removal of a variety of environmental pollutants such as bisphenol A [11], pesticides [12], explosives [13], and heavy metals [14]. The plant under present study is an annual, wooly herb, belonging to the family Asteraceae and mainly found in tropical and subtropical regions.…”
Section: Introductionmentioning
confidence: 99%
“…For more accurate and precise studies on phytoremediation, aseptic cultures of plants provide a convenient and efficient alternative [10]. The cell suspension cultures proved to be an effective tool for removal of a variety of environmental pollutants such as bisphenol A [11], pesticides [12], explosives [13], and heavy metals [14]. The plant under present study is an annual, wooly herb, belonging to the family Asteraceae and mainly found in tropical and subtropical regions.…”
Section: Introductionmentioning
confidence: 99%